Preparation process of tritium-proof composite fabric

By chlorinating on the surface of polyethylene film and reacting with resorcinol, combining aminomethyl trimethylsilane and non-woven intermediate layer hot-rolling bonding technology, the aging problem of tritium-proof fabrics is solved, and the anti-aging and mechanics are improved Performance enhances protection effect.

CN119189457AActive Publication Date: 2024-12-27HUNAN INSTITUTE OF ENGINEERING
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411398502.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-27
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing tritium-proof fabrics age during long-term use, resulting in a decrease in protective performance and mechanical properties, making it difficult to meet the needs of tritium-proof.

Method used

The surface of polyethylene film is chlorinated in situ grafted 2-chloro-6-vinylpyridine and reacted with resorcinol to form a modified chlorinated polyethylene film, and then reacted with ammoniamethyltrimethylsilane to form The modified adhesive film is hot-rolled bonded by hot-rolling and bonding of the non-woven fabric intermediate layer and the polyvinylidene chloride film layer to form a tritium-proof composite fabric.

Benefits of technology

It improves the anti-ultraviolet aging, thermal oxygen aging and mechanical properties of tritium-resistant fabrics, enhances the hydrophobicity and heat resistance of the fabrics, and reduces the gas permeability and improves the protective effect.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation process of an anti-tritium composite fabric, and relates to the field of fabric preparation. When the tritium-proof composite fabric is prepared, a non-woven fabric is used as a middle layer, the two surfaces of the non-woven fabric are sequentially covered with a polyvinylidene chloride film layer and a modified chlorinated polyethylene film layer, and the layers are subjected to hot rolling bonding through a modified adhesive film; the modified chlorinated polyethylene film is prepared by performing chlorination in-situ grafting on the surface of a polyethylene film with 2-chloro-6-vinylpyridine, reacting with resorcinol, and reacting with aminomethyltrimethylsilane; the modified adhesive film is prepared by copolymerizing vinyl acetate, ethylene and vinyl quaternary ammonium salt, then reacting with 2-tert-butylphenol, and then granulating and mould pressing to form a film; the anti-tritium composite fabric prepared by the invention has excellent anti-aging performance, mechanical performance and anti-tritium performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabric preparation, and in particular to a preparation process of tritium-proof composite fabric. Background Art

[0002] With the increasing use of tritium for both military and civilian purposes, the development of tritium-proof materials has become a hot topic in the field of tritium-proof research. Tritium gas and tritium water are easily adsorbed on the surface of materials and then penetrate into the human body. Currently, tritium-proof materials have gradually developed from natural rubber and chloroprene rubber to polymer materials, but single polymer materials have single performance. Therefore, researchers have focused their research on composite materials composed of polymer materials.

[0003] In personal anti-tritium protective materials such as gloves and protective clothing, fabrics are the main part of the protective materials. Traditional single-component fabrics have poor anti-tritium performance and cannot meet the protection needs. The anti-tritium performance of the fabric can be improved by compounding other polymer materials. However, during long-term use, the fabric is prone to aging, resulting in a decrease in protective and mechanical properties. Therefore, while ensuring the anti-permeability performance of the anti-tritium fabric, improving the anti-aging performance of the fabric is an important issue in the research and development of anti-tritium protective fabrics. Summary of the invention

[0004] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a preparation process for tritium-proof composite fabric.

[0005] The technical solution of the present invention to solve the technical problem is to provide a preparation process of tritium-proof composite fabric, which includes the following preparation steps: (1) Immerse a polyethylene film in a 2-chloro-6-vinylpyridine-acetone solution, let it stand for 3 hours, then take it out, place the taken polyethylene film under an ultraviolet lamp, the ultraviolet lamp power is 8W, the light source distance is 10 cm, and chlorine gas is introduced at a flow rate of 0.5 mL / s for 5-10 minutes, then the temperature is raised to 80°C, react for 2-3 hours, and then the temperature is further raised to 120°C, and the reaction is continued for 3 hours. After the reaction is completed, remove the ultraviolet lamp, stop introducing chlorine gas, and use a vacuum pump to evacuate for 30-40 minutes. After cooling to 100°C, introduce air and use a vacuum pump to evacuate for 50-60 minutes. After cooling to room temperature, take out the film and wash it with acetone for 3-4 times to obtain a pyridyl chlorinated polyethylene film; (2) Mix resorcinol, pyridyl chlorinated polyethylene film, anhydrous aluminum chloride and acetone in a mass ratio of 1:(10-12):(1.2-1.3):(12-15), react at 70-80°C for 5-6h, filter and wash with pure water for 3-4 times, and dry at room temperature for 24h to obtain a pre-modified chlorinated polyethylene film; mix polyformaldehyde and chloroform evenly and heat to 40°C, add calcium hydride, heat to 70°C, add aminomethyltrimethylsilane under nitrogen protection, heat to 80°C, add the pre-modified chlorinated polyethylene film, react for 20h, take out, wash with pure water 3 times and dry at room temperature for 24h to obtain a modified chlorinated polyethylene film; (3) Vinyl acetate, vinyl quaternary ammonium salt, methanol, and azobisisobutyronitrile are mixed in a mass ratio of 1: (0.2-0.3): (0.7-0.8): (0.01-0.02), and put into a high-pressure reactor. After ethylene is introduced for 5-10 minutes, the pressure of ethylene in the high-pressure reactor is set to 4.0 MPa, the temperature is raised to 55-60° C., and the reaction is carried out at a speed of 150-200 r / min for 4-5 hours. After the reaction is completed, the temperature is lowered to room temperature and the material is discharged. A methanol aqueous solution is used for precipitation, and the mixture is filtered and washed with pure water for 3-4 times. The mixture is dried at 70° C. for 24 hours to obtain a quaternary ammonium salt-ethylene-vinyl acetate copolymer; (4) Paraformaldehyde and N,N-dimethylformamide are mixed uniformly and heated to 40°C, calcium hydride is added, the temperature is raised to 70°C, nitrogen is introduced, 2-tert-butylphenol is added, the temperature is raised to 80°C, quaternary ammonium salt-ethylene-vinyl acetate copolymer is added, the reaction is continued for 20 hours, the filtrate is filtered and retained, N,N-dimethylformamide is removed by vacuum rotary evaporation to obtain a modified ethylene-vinyl acetate copolymer, the modified ethylene-vinyl acetate copolymer is granulated by a granulator, and the granules are compression molded by a flat vulcanizer at 90°C to obtain a modified film; (5) Grinding one side of the non-woven fabric with sandpaper, covering it with a modified adhesive film, then covering it with a polyvinylidene chloride film, then covering it with a modified adhesive film, and then covering it with a modified chlorinated polyethylene film. Repeat the above grinding-covering operation on the other side of the non-woven fabric, and hot rolling it twice on a hot rolling mill. The hot rolling mill pressure is 0.3 MPa, the temperature is 140-150°C, and the time is 3 minutes. After the hot rolling is completed, an anti-tritium composite fabric is obtained.

[0006] As an optimization, the 2-chloro-6-vinylpyridine-acetone solution in step (1) is prepared by mixing 2-chloro-6-vinylpyridine and acetone in a mass ratio of 1:(5-6); the model of the polyethylene film is 6098.

[0007] As an optimization, the mass ratio of the polyformaldehyde, aminomethyltrimethylsilane, pre-modified chlorinated polyethylene film, calcium hydride and chloroform in step (2) is 1:(1.6-1.8):(10-12):(0.7-0.8):(20-30).

[0008] As an optimization, the preparation process of the vinyl quaternary ammonium salt in step (3) is as follows: at 0°C, N,N-dimethylethylenediamine, di-tert-butyl dicarbonate, and dichloromethane are mixed in a mass ratio of 1:(0.6-0.7):(20-30) for 10-15 minutes, stirred at 20°C for 24 hours, and pure water of an equal volume to dichloromethane is added, and the liquids are separated and the organic phase is retained; vinyl chloride of 0.9-1.0 times the mass of N,N-dimethylethylenediamine and potassium carbonate of 0.2-0.3 times the mass of N,N-dimethylethylenediamine are added to the organic phase, and the temperature is raised. The mixture is refluxed to 70-80° C. for reaction for 10-12 hours. After the reaction is completed, dichloromethane is removed by rotary evaporation under reduced pressure to obtain a vinyl quaternary ammonium salt precursor. At 0-4° C., a vinyl quaternary ammonium salt precursor and dichloromethane are mixed in a mass ratio of 1:(10-12), and trifluoroacetic acid in an amount of 5-7 times the mass of the vinyl quaternary ammonium salt precursor is added dropwise at a rate of 1 mL / min. After the addition is completed, the mixture is heated to room temperature and the reaction is continued for 3-4 hours. After the reaction is completed, a saturated sodium carbonate solution is added to adjust the pH to 9-10, and dichloromethane is removed by rotary evaporation under reduced pressure to obtain a vinyl quaternary ammonium salt.

[0009] As an optimization, the methanol-water solution in step (3) is prepared by mixing methanol and water in a mass ratio of 3:1.

[0010] As an optimization, the mass ratio of the polyformaldehyde, 2-tert-butylphenol, quaternary ammonium salt-ethylene-vinyl acetate copolymer, calcium hydride, and N,N-dimethylformamide in step (4) is 1:(3.4-3.5):(0.2-0.3):(0.7-0.8):(20-30).

[0011] As an optimization, the thickness of the modified film in step (4) is 0.5 mm.

[0012] As an optimization, the model of the non-woven fabric in step (5) is 1473R; the model of the polyvinylidene chloride film is VSL-4603.

[0013] Compared with the prior art, the present invention has the following beneficial effects: When preparing the tritium-proof composite fabric, the present invention firstly chlorinates and grafts 2-chloro-6-vinylpyridine on the surface of a polyethylene film in situ, reacts with resorcinol, and then reacts with aminomethyltrimethylsilane to obtain a modified chlorinated polyethylene film; secondly, N,N-dimethylethylenediamine protected by di-tert-butyl dicarbonate reacts with vinyl chloride, and then deprotects with trifluoroacetic acid to obtain a vinyl quaternary ammonium salt, and then copolymerizes vinyl acetate, ethylene and the vinyl quaternary ammonium salt and reacts with 2-tert-butylphenol, and then granulates and molds the film to obtain a modified adhesive film; finally, a non-woven fabric is used as an intermediate layer, and both sides are sequentially covered with a polyvinylidene chloride film layer and a modified chlorinated polyethylene film layer, and the layers are hot-rolled and bonded by the modified adhesive film to obtain the tritium-proof composite fabric; Firstly, 2-chloro-6-vinylpyridine is grafted on the surface of polyethylene film by chlorination in situ, and then reacted with resorcinol, and then reacted with aminomethyltrimethylsilane to obtain modified chlorinated polyethylene film; chlorine gas is decomposed by heat to generate chlorine free radicals, which attack the molecular chain of polyethylene film and capture the hydrogen atom of tertiary carbon on the molecular chain to generate macromolecular free radicals and hydrogen chloride; the carbon-carbon double bond on 2-chloro-6-vinylpyridine can react with the macromolecular free radicals; while the polyethylene film is chlorinated, 2-chloro-6-vinylpyridine is grafted on the surface; 2-chloro-6-vinylpyridine and resorcinol undergo Friedel-Crafts alkylation reaction; in the generated structure, N on pyridine and phenolic hydroxyl on the ortho position form an intramolecular chelate ring, which can convert light energy into heat energy, has a good absorption effect on ultraviolet rays, and can provide good anti-ultraviolet aging performance for anti-tritium fabrics; finally, it reacts with aminomethyltrimethylsilane in the presence of polyformaldehyde to generate benzoxazine and grafted with trimethylsilane; trimethoxysilane can further improve the hydrophobicity and heat resistance of the fabric.

[0014] Secondly, N,N-dimethylethylenediamine protected by di-tert-butyl dicarbonate is reacted with vinyl chloride, and then deprotected by trifluoroacetic acid to obtain vinyl quaternary ammonium salt. Vinyl acetate, ethylene and vinyl quaternary ammonium salt are copolymerized and reacted with 2-tert-butylphenol, and then granulated and molded into films to obtain modified adhesive films; di-tert-butyl dicarbonate is used to protect the primary amino group on N,N-dimethylethylenediamine, and the tertiary amine group on N,N-dimethylethylenediamine reacts with vinyl chloride to generate a quaternary ammonium salt containing vinyl, which can give the fabric good antibacterial properties. Then, the primary amine group is re-exposed by deprotecting it by trifluoroacetic acid; vinyl quaternary ammonium salt, ethylene and vinyl acetate are copolymerized to form a polymer with hot melt properties, and the primary amino group on the polymer side chain and 2-tert-butylphenol form a benzoxazine functional group in the presence of paraformaldehyde.

[0015] Finally, the non-woven fabric is used as the middle layer, and the two sides are covered with a polyvinylidene chloride film layer and a modified chlorinated polyethylene film layer in turn, and the interlayers are bonded by hot rolling of the modified adhesive film to obtain an anti-tritium composite fabric; the modified adhesive film melts at high temperature, and its fluidity is enhanced, so it can penetrate and wet the surface of the non-woven fabric, the polyvinylidene chloride film layer and the modified chlorinated polyethylene film layer, thereby making the layers bonded to each other; for the interlayer between the non-woven fabric and the polyvinylidene chloride film layer, the benzoxazine on the side chain of the modified adhesive film is ring-opened and self-cross-linked at high temperature to form a three-dimensional network structure, and increasing the cross-linking density can further improve the protective effect; for the polyvinylidene chloride film layer and the modified chlorinated polyethylene film layer, the benzoxazine on the modified chlorinated polyethylene is ring-opened at high temperature and cross-linked with the modified adhesive film to increase the adhesion and improve the protective effect; the benzoxazine on the modified adhesive film is ring-opened to form a cross-linked structure, and the cross-linking point at one end is located on the N atom, and the cross-linking point at the other end is located at the para position of the phenolic hydroxyl group on 2-tert-butylphenol, which can form a hindered phenol structure, thereby giving the fabric resistance to thermal oxidative aging. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the present invention.

[0017] The model of the polyethylene film used in the following comparative examples is 6098; the methanol aqueous solution used is prepared by mixing methanol and water in a mass ratio of 3:1; the model of the non-woven fabric used is 1473R; and the model of the polyvinylidene chloride film used is VSL-4603.

[0018] Embodiment 1: A tritium-proof composite fabric comprises the following preparation steps: (1) 2-chloro-6-vinylpyridine and acetone are mixed in a mass ratio of 1:5 to obtain a 2-chloro-6-vinylpyridine-acetone solution; a polyethylene film is immersed in the 2-chloro-6-vinylpyridine-acetone solution, and after standing for 3 hours, the polyethylene film is taken out, and the taken out polyethylene film is placed under an ultraviolet lamp, the ultraviolet lamp power is 8 W, the light source distance is 10 cm, and chlorine gas is introduced at a flow rate of 0.5 mL / s for 10 minutes, and then the temperature is raised to 80°C, and after reacting for 3 hours, the temperature is further raised to 120°C, and the reaction is continued for 3 hours. After the reaction is completed, the ultraviolet lamp is removed, the introduction of chlorine gas is stopped, and vacuum pumping is used for 40 minutes. After cooling to 100°C, air is introduced and vacuum pumping is used for 60 minutes. After cooling to room temperature, the film is taken out and washed with acetone for 4 times to obtain a pyridine-based chlorinated polyethylene film; (2) Resorcinol, pyridyl chlorinated polyethylene film, anhydrous aluminum chloride and acetone were mixed in a mass ratio of 1:10:1.2:12, reacted at 80°C for 6 hours, filtered and washed with pure water for 4 times, and dried at room temperature for 24 hours to obtain a pre-modified chlorinated polyethylene film; polyformaldehyde, aminomethyltrimethylsilane, pre-modified chlorinated polyethylene film, calcium hydride and chloroform were weighed in a mass ratio of 1:1.6:10:0.7:20; polyformaldehyde and chloroform were mixed evenly and heated to 40°C, calcium hydride was added, heated to 70°C, aminomethyltrimethylsilane was added under nitrogen protection, heated to 80°C, and pre-modified chlorinated polyethylene film was added. After reacting for 20 hours, the film was taken out, washed with pure water for 3 times and dried at room temperature for 24 hours to obtain a modified chlorinated polyethylene film; (3) At 0°C, N,N-dimethylethylenediamine, di-tert-butyl dicarbonate, and dichloromethane were mixed in a mass ratio of 1:0.6:20 for 15 min, stirred at 20°C for 24 h, and pure water of equal volume to dichloromethane was added, and the liquids were separated and the organic phase was retained; vinyl chloride of 0.9 times the mass of N,N-dimethylethylenediamine and potassium carbonate of 0.2 times the mass of N,N-dimethylethylenediamine were added to the organic phase, and the temperature was raised to 80°C for reflux reaction for 12 h. After the reaction was completed, dichloromethane was removed by vacuum rotary evaporation to obtain a vinyl quaternary ammonium salt precursor; at 4°C, a vinyl quaternary ammonium salt precursor and dichloromethane were mixed in a mass ratio of 1:10, and trifluoroacetic acid of 5 times the mass of the vinyl quaternary ammonium salt precursor was added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the temperature is raised to room temperature and the reaction is continued for 4 hours. After the reaction is completed, a saturated sodium carbonate solution is added to adjust the pH to 10, and dichloromethane is removed by reduced pressure rotary evaporation to obtain a vinyl quaternary ammonium salt; vinyl acetate, vinyl quaternary ammonium salt, methanol, and azobisisobutyronitrile are mixed in a mass ratio of 1:0.2:0.7:0.01, and put into a high-pressure reactor. After ethylene is introduced for 10 minutes, the pressure of ethylene in the high-pressure reactor is set to 4.0MPa, the temperature is raised to 60°C, and the reaction is carried out at a speed of 200r / min for 5 hours. After the reaction is completed, the temperature is lowered to room temperature and the material is discharged, and a methanol aqueous solution is used for precipitation, filtration is performed, and pure water is used for 4 times, and drying is performed at 70°C for 24 hours to obtain a quaternary ammonium salt-ethylene-vinyl acetate copolymer; (4) Weighing polyformaldehyde, 2-tert-butylphenol, quaternary ammonium salt-ethylene-vinyl acetate copolymer, calcium hydride, and N,N-dimethylformamide in a mass ratio of 1:3.4:0.2:0.7:20; mixing polyformaldehyde and N,N-dimethylformamide uniformly and heating to 40°C, adding calcium hydride, heating to 70°C, introducing nitrogen, adding 2-tert-butylphenol, heating to 80°C, adding quaternary ammonium salt-ethylene-vinyl acetate copolymer, reacting for 20 hours, filtering and retaining the filtrate, removing N,N-dimethylformamide by vacuum rotary evaporation to obtain a modified ethylene-vinyl acetate copolymer, granulating the modified ethylene-vinyl acetate copolymer using a granulator, and compression molding the granules using a flat vulcanizer at 90°C to obtain a modified film, the thickness of the modified film being 0.5 mm; (5) One side of the non-woven fabric is polished with sandpaper, covered with a modified adhesive film, then covered with a polyvinylidene chloride film, then covered with a modified adhesive film, and then covered with a modified chlorinated polyethylene film. The other side of the non-woven fabric is repeated with the above polishing-covering operation, and hot-rolled twice on a hot rolling mill. The hot rolling mill pressure is 0.3 MPa, the temperature is 150°C, and the time is 3 minutes. After the hot rolling is completed, an anti-tritium composite fabric is obtained.

[0019] Embodiment 2: A tritium-proof composite fabric comprises the following preparation steps: (1) 2-chloro-6-vinylpyridine and acetone were mixed in a mass ratio of 1:5.5 to obtain a 2-chloro-6-vinylpyridine-acetone solution; a polyethylene film was immersed in the 2-chloro-6-vinylpyridine-acetone solution, and after standing for 3 hours, the polyethylene film was taken out, and the taken out polyethylene film was placed under an ultraviolet lamp with a power of 8 W and a light source distance of 10 cm. After passing chlorine gas at a flow rate of 0.5 mL / s for 7 minutes, the temperature was raised to 80°C, and after reacting for 2.5 hours, the temperature was further raised to 120°C and the reaction was continued for 3 hours. After the reaction was completed, the ultraviolet lamp was removed, the passing of chlorine gas was stopped, and vacuum pumping was used for 35 minutes. After cooling to 100°C, air was passed and vacuum pumping was used for 55 minutes. After cooling to room temperature, the film was taken out and washed with acetone for 3 times to obtain a pyridyl chlorinated polyethylene film; (2) Resorcinol, pyridyl chlorinated polyethylene film, anhydrous aluminum chloride and acetone were mixed in a mass ratio of 1:11:1.25:13, reacted at 75°C for 5.5 hours, filtered and washed with pure water for 3 times, and dried at room temperature for 24 hours to obtain a pre-modified chlorinated polyethylene film; polyformaldehyde, aminomethyltrimethylsilane, pre-modified chlorinated polyethylene film, calcium hydride and chloroform were weighed in a mass ratio of 1:1.5:11:0.75:25; polyformaldehyde and chloroform were mixed evenly and heated to 40°C, calcium hydride was added, heated to 70°C, aminomethyltrimethylsilane was added under nitrogen protection, heated to 80°C, and pre-modified chlorinated polyethylene film was added. After reacting for 20 hours, the film was taken out, washed with pure water for 3 times and dried at room temperature for 24 hours to obtain a modified chlorinated polyethylene film; (3) At 0°C, N,N-dimethylethylenediamine, di-tert-butyl dicarbonate, and dichloromethane were mixed in a mass ratio of 1:0.65:25 for 13 minutes, stirred at 20°C for 24 hours, and pure water of equal volume to dichloromethane was added, and the liquids were separated and the organic phase was retained; vinyl chloride (0.95 times the mass of N,N-dimethylethylenediamine) and potassium carbonate (0.25 times the mass of N,N-dimethylethylenediamine) were added to the organic phase, and the temperature was raised to 75°C for reflux reaction for 11 hours. After the reaction was completed, dichloromethane was removed by vacuum rotary evaporation to obtain a vinyl quaternary ammonium salt precursor; at 3°C, a vinyl quaternary ammonium salt precursor and dichloromethane were mixed in a mass ratio of 1:11, and trifluoroacetic acid (6 times the mass of the vinyl quaternary ammonium salt precursor) was added dropwise at a dropping speed of 1 mL / min. After the addition is completed, the temperature is raised to room temperature and the reaction is continued for 3.5 hours. After the reaction is completed, a saturated sodium carbonate solution is added to adjust the pH to 9.5, and dichloromethane is removed by reduced pressure rotary evaporation to obtain a vinyl quaternary ammonium salt; vinyl acetate, vinyl quaternary ammonium salt, methanol, and azobisisobutyronitrile are mixed in a mass ratio of 1:0.25:0.75:0.015, and put into a high-pressure reactor. After ethylene is introduced for 7 minutes, the pressure of ethylene in the high-pressure reactor is set to 4.0MPa, the temperature is raised to 57°C, and the reaction is carried out at a speed of 170r / min for 4.5 hours. After the reaction is completed, the temperature is lowered to room temperature and the material is discharged, and a methanol aqueous solution is used for precipitation, and the mixture is filtered and washed with pure water for 3 times, and dried at 70°C for 24 hours to obtain a quaternary ammonium salt-ethylene-vinyl acetate copolymer; (4) Weighing polyformaldehyde, 2-tert-butylphenol, quaternary ammonium salt-ethylene-vinyl acetate copolymer, calcium hydride, and N,N-dimethylformamide in a mass ratio of 1:3.45:0.25:0.75:25; uniformly mixing polyformaldehyde and N,N-dimethylformamide and heating to 40°C, adding calcium hydride, heating to 70°C, introducing nitrogen, adding 2-tert-butylphenol, heating to 80°C, adding quaternary ammonium salt-ethylene-vinyl acetate copolymer, reacting for 20 hours, filtering and retaining the filtrate, removing N,N-dimethylformamide by vacuum rotary evaporation to obtain a modified ethylene-vinyl acetate copolymer, granulating the modified ethylene-vinyl acetate copolymer using a granulator, and compression molding the granules using a flat vulcanizer at 90°C to obtain a modified film, the thickness of the modified film being 0.5 mm; (5) One side of the non-woven fabric is polished with sandpaper, covered with a modified adhesive film, then covered with a polyvinylidene chloride film, then covered with a modified adhesive film, and then covered with a modified chlorinated polyethylene film. The other side of the non-woven fabric is repeated with the above polishing-covering operation, and hot-rolled three times on a hot rolling mill with a pressure of 0.3 MPa, a temperature of 145°C, and a time of 3 minutes. After the hot rolling is completed, an anti-tritium composite fabric is obtained.

[0020] Embodiment 3: A tritium-proof composite fabric comprises the following preparation steps: (1) 2-chloro-6-vinylpyridine and acetone are mixed in a mass ratio of 1:6 to obtain a 2-chloro-6-vinylpyridine-acetone solution; a polyethylene film is immersed in the 2-chloro-6-vinylpyridine-acetone solution, and after standing for 3 hours, the polyethylene film is taken out, and the taken out polyethylene film is placed under an ultraviolet lamp with a power of 8 W and a light source distance of 10 cm. After passing chlorine gas at a flow rate of 0.5 mL / s for 5 minutes, the temperature is raised to 80°C, and after reacting for 2 hours, the temperature is further raised to 120°C and the reaction is continued for 3 hours. After the reaction is completed, the ultraviolet lamp is removed, the passing of chlorine gas is stopped, and a vacuum pump is used to evacuate for 30 minutes. After cooling to 100°C, air is passed and a vacuum pump is used to evacuate for 50 minutes. After cooling to room temperature, the film is taken out and washed with acetone three times to obtain a pyridyl chlorinated polyethylene film; (2) Resorcinol, pyridyl chlorinated polyethylene film, anhydrous aluminum chloride and acetone were mixed in a mass ratio of 1:12:1.3:15, reacted at 70°C for 5 hours, filtered and washed with pure water for 3 times, and dried at room temperature for 24 hours to obtain a pre-modified chlorinated polyethylene film; polyformaldehyde, aminomethyltrimethylsilane, pre-modified chlorinated polyethylene film, calcium hydride and chloroform were weighed in a mass ratio of 1:1.8:12:0.8:30; polyformaldehyde and chloroform were mixed evenly and heated to 40°C, calcium hydride was added, heated to 70°C, aminomethyltrimethylsilane was added under nitrogen protection, heated to 80°C, and pre-modified chlorinated polyethylene film was added. After reacting for 20 hours, the film was taken out, washed with pure water for 3 times and dried at room temperature for 24 hours to obtain a modified chlorinated polyethylene film; (3) At 0°C, N,N-dimethylethylenediamine, di-tert-butyl dicarbonate, and dichloromethane were mixed in a mass ratio of 1:0.7:30 for 10 min, stirred at 20°C for 24 h, and pure water of equal volume to dichloromethane was added, and the liquids were separated and the organic phase was retained; vinyl chloride of 1.0 times the mass of N,N-dimethylethylenediamine and potassium carbonate of 0.3 times the mass of N,N-dimethylethylenediamine were added to the organic phase, and the temperature was raised to 70°C for reflux reaction for 10 h. After the reaction was completed, dichloromethane was removed by vacuum rotary evaporation to obtain a vinyl quaternary ammonium salt precursor; at 0°C, a vinyl quaternary ammonium salt precursor and dichloromethane were mixed in a mass ratio of 1:12, and trifluoroacetic acid of 7 times the mass of the vinyl quaternary ammonium salt precursor was added dropwise at a dropping rate of 1 mL / min n, after the addition is completed, the temperature is raised to room temperature and the reaction is continued for 3 hours. After the reaction is completed, a saturated sodium carbonate solution is added to adjust the pH to 9, and dichloromethane is removed by vacuum rotary evaporation to obtain a vinyl quaternary ammonium salt; vinyl acetate, vinyl quaternary ammonium salt, methanol, and azobisisobutyronitrile are mixed in a mass ratio of 1:0.3:0.8:0.02, and put into a high-pressure reactor. After ethylene is introduced for 5 minutes, the pressure of ethylene in the high-pressure reactor is set to 4.0MPa, the temperature is raised to 55°C, and the reaction is carried out at a speed of 150r / min for 4 hours. After the reaction is completed, the temperature is lowered to room temperature and the material is discharged, and a methanol aqueous solution is used for precipitation, filtration is performed, and pure water is used for washing 3 times, and drying is performed at 70°C for 24 hours to obtain a quaternary ammonium salt-ethylene-vinyl acetate copolymer; (4) Weighing polyformaldehyde, 2-tert-butylphenol, quaternary ammonium salt-ethylene-vinyl acetate copolymer, calcium hydride, and N,N-dimethylformamide in a mass ratio of 1:3.5:0.3:0.8:30; uniformly mixing polyformaldehyde and N,N-dimethylformamide and heating to 40°C, adding calcium hydride, heating to 70°C, introducing nitrogen, adding 2-tert-butylphenol, heating to 80°C, adding quaternary ammonium salt-ethylene-vinyl acetate copolymer, reacting for 20 hours, filtering and retaining the filtrate, removing N,N-dimethylformamide by vacuum rotary evaporation to obtain a modified ethylene-vinyl acetate copolymer, granulating the modified ethylene-vinyl acetate copolymer using a granulator, and compression molding the granules using a flat vulcanizer at 90°C to obtain a modified film, the thickness of the modified film being 0.5 mm; (5) One side of the non-woven fabric is polished with sandpaper, covered with a modified adhesive film, then covered with a polyvinylidene chloride film, then covered with a modified adhesive film, and then covered with a modified chlorinated polyethylene film. The other side of the non-woven fabric is repeated with the above polishing-covering operation, and hot-rolled twice on a hot rolling mill with a pressure of 0.3 MPa, a temperature of 140°C, and a time of 3 minutes. After the hot rolling is completed, an anti-tritium composite fabric is obtained.

[0021] Comparative Example 1: The preparation process of the tritium-proof composite fabric of Comparative Example 1 differs from that of Example 2 in that step (2) is not included, and step (1) is modified as follows: 2-chloro-6-vinylpyridine and acetone are mixed at a mass ratio of 1:5.5 to obtain a 2-chloro-6-vinylpyridine-acetone solution; a polyethylene film is immersed in the 2-chloro-6-vinylpyridine-acetone solution, and the film is taken out after standing for 3 hours. The taken out polyethylene film is placed under an ultraviolet lamp with a power of 8 W and a light source distance of 10 cm. After chlorine gas is introduced at a flow rate of 0.5 mL / s for 7 minutes, the temperature is raised to 80° C., and the reaction is continued for 2.5 hours. The temperature is further raised to 120° C. and the reaction is continued for 3 hours. After the reaction is completed, the ultraviolet lamp is removed, the introduction of chlorine gas is stopped, and the air is evacuated using a vacuum pump for 35 minutes. After the temperature is lowered to 100° C., air is introduced and the air is evacuated using a vacuum pump for 55 minutes. After the temperature is lowered to room temperature, the film is taken out and washed with acetone three times to obtain a modified chlorinated polyethylene film.

[0022] Comparative Example 2: The difference between the preparation process of the anti-tritium composite fabric of Comparative Example 2 and Example 2 is that step (2) is modified as follows: resorcinol, pyridyl chlorinated polyethylene film, anhydrous aluminum chloride, and acetone are mixed in a mass ratio of 1:11:1.25:13, reacted at 75°C for 5.5 hours, filtered and washed with pure water for 3 times, and dried at room temperature for 24 hours to obtain a modified chlorinated polyethylene film.

[0023] Comparative Example 3: The difference between the preparation process of the tritium-proof composite fabric of Comparative Example 3 and Example 2 is that step (4) is modified to use a granulator to granulate the quaternary ammonium salt-ethylene-vinyl acetate copolymer, and use a flat vulcanizer to mold the granules at 90° C. to obtain a modified film, and the thickness of the modified film is 0.5 mm.

[0024] Test Example 1: Mechanical properties test: Test method: According to the standard GB / T 3923.1, the anti-tritium composite fabrics prepared in the embodiment and the comparative example are made into standard samples; the breaking strength of the samples is measured by using a YG(B)026HC-500 fabric strength tester; wherein the clamping distance is 200mm, the speed is 100mm / min, the sample width is 50.00mm, the ambient temperature is (20±3)℃, and the relative humidity is (65±5)%. According to the standard FZ / T 01085-2009, the YG(B)026HC-500 fabric strength tester is used to test the peel strength between the polyvinylidene chloride film and the modified chlorinated polyethylene layer of the anti-tritium fabrics prepared in the embodiment and the comparative example. The results are shown in Table 1.

[0025] Table 1 Breaking strength (N) Peel strength (N / 2.5cm) Example 1 354.61 32.47 Example 2 357.29 33.16 Example 3 355.76 32.69 Comparative Example 1 237.47 6.46 Comparative Example 2 241.23 7.16 Comparative Example 3 254.66 6.13 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the anti-tritium composite fabric prepared by the present invention has good mechanical properties.

[0026] By comparison, the breaking strength of Examples 1 to 3 is greater than that of Comparative Examples 1 to 3, and the peel strength between the vinylidene chloride film and the modified chlorinated polyethylene layer of Examples 1 to 3 is greater than the peel strength between the vinylidene chloride film and the modified chlorinated polyethylene layer of Comparative Examples 1 to 3, indicating that the non-woven fabric is used as the middle layer, the polyvinylidene chloride film layer and the modified chlorinated polyethylene film layer are sequentially covered on both sides, and the interlayers are hot-rolled and bonded by the modified adhesive film to obtain the anti-tritium composite fabric; the modified adhesive film melts at high temperature, and the fluidity is enhanced, and it can penetrate and wet the surface of the non-woven fabric, the polyvinylidene chloride film layer and the modified chlorinated polyethylene film layer, so that the layers are bonded to each other; for the interlayer between the non-woven fabric and the polyvinylidene chloride film layer, the benzoxazine on the side chain of the modified adhesive film is ring-opened and self-crosslinked at high temperature to form a three-dimensional network structure, thereby increasing the crosslinking density.

[0027] Test Example 2: Test of anti-ultraviolet aging performance: Test method: All the tritium-proof composite fabrics prepared in the examples and comparative examples were laid flat on a sample rack, and the sample rack was placed in a UV light box parallel to the UV lamp tube, with a radiation intensity of 1100 W / m 2The temperature in the box is 60℃, the humidity is 60%, the fabric is 10cm away from the lamp, and the irradiation time is 60h. After the irradiation, the breaking strength is tested according to the breaking strength test method of the mechanical properties test and the breaking strength retention rate is calculated. The results are shown in Table 2.

[0028] Test of thermal oxidation aging resistance: Test method: All the tritium-proof composite fabrics prepared in the examples and comparative examples were laid flat on a sample rack and then placed in an aging box at an aging temperature of 50°C, a relative humidity of 55%, an ozone concentration of 450 pphm, and an aging time of 360 hours. After aging, the breaking strength was tested according to the breaking strength test method of the mechanical property test and the breaking strength retention rate was calculated. The results are shown in Table 2.

[0029] Table 2 Retention rate of breaking strength after UV irradiation (%) Retention rate of breaking strength after thermal oxidation aging (%) Example 1 97.47 94.54 Example 2 97.14 95.23 Example 3 96.86 94.81 Comparative Example 1 73.25 89.23 Comparative Example 2 96.56 89.46 Comparative Example 3 96.62 71.24 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the anti-tritium composite fabric prepared by the present invention has good anti-aging performance.

[0030] By comparison, the breaking strength retention rate after ultraviolet irradiation of Examples 1 to 3 is greater than that of Comparative Example 1, and the breaking strength retention rate after thermal oxidative aging of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that firstly, after chlorination and in-situ grafting of 2-chloro-6-vinylpyridine on the surface of the polyethylene film, it reacts with resorcinol, and the N on the pyridine and the phenolic hydroxyl group at the ortho position in the generated structure form an intramolecular chelate ring, which can convert light energy into heat energy, has a good absorption effect on ultraviolet rays, and can provide good anti-ultraviolet aging performance for the anti-tritium fabric; secondly, the benzoxazine on the modified film is ring-opened to form a cross-linked structure, one end of the cross-linking point is located on the N atom, and the other end of the cross-linking point is located at the para position of the phenolic hydroxyl group on the 2-tert-butylphenol, which can form a hindered phenol structure, thereby giving the fabric resistance to thermal oxidative aging.

[0031] Test Example 3: Gas permeability test: Test method: The gas permeability of the anti-tritium composite fabrics prepared in all embodiments and comparative examples was tested according to the standard GB / T1038-2000, with hydrogen gas selected as the gas and the test temperature being 23° C. The results are shown in Table 3.

[0032] Table 3 Gas permeability / (10-13cm³·cm / (cm²·s·Pa)) Gas permeability / (10-13cm³·cm / (cm²·s·Pa)) Example 1 7.084 Comparative Example 1 13.569 Example 2 7.136 Comparative Example 2 13.457 Example 3 7.109 Comparative Example 3 11.026 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the anti-tritium composite fabric prepared by the present invention has good gas permeation resistance.

[0033] By comparison, the gas permeability of Examples 1 to 3 is lower than that of Comparative Examples 1 to 4, indicating that the non-woven fabric is used as the middle layer, the polyvinylidene chloride film layer and the modified chlorinated polyethylene film layer are sequentially covered on both sides, and the interlayers are bonded by hot rolling of the modified adhesive film to obtain the anti-tritium composite fabric; the modified adhesive film melts at high temperature, and the fluidity is enhanced, and it can penetrate and wet the surface of the non-woven fabric, the polyvinylidene chloride film layer and the modified chlorinated polyethylene film layer, so that the layers are bonded to each other; for the interlayer between the non-woven fabric and the polyvinylidene chloride film layer, the benzoxazine on the side chain of the modified adhesive film is ring-opened and self-cross-linked at high temperature to form a three-dimensional network structure, and increasing the cross-linking density can further improve the protective effect; for the polyvinylidene chloride film layer and the modified chlorinated polyethylene film layer, the benzoxazine on the modified chlorinated polyethylene is ring-opened and cross-linked with the modified adhesive film at high temperature to increase the adhesion and improve the protective effect.

[0034] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A preparation process of tritium-proof composite fabric, characterized in that: The method comprises the following preparation steps: (1) Immerse a polyethylene film in a 2-chloro-6-vinylpyridine-acetone solution, let it stand for 3 hours, then take it out, place the taken polyethylene film under an ultraviolet lamp, the ultraviolet lamp power is 8W, the light source distance is 10 cm, and chlorine gas is introduced at a flow rate of 0.5 mL / s for 5-10 minutes, then the temperature is raised to 80°C, react for 2-3 hours, and then the temperature is further raised to 120°C, and the reaction is continued for 3 hours. After the reaction is completed, remove the ultraviolet lamp, stop introducing chlorine gas, and use a vacuum pump to evacuate for 30-40 minutes. After cooling to 100°C, introduce air and use a vacuum pump to evacuate for 50-60 minutes. After cooling to room temperature, take out the film and wash it with acetone for 3-4 times to obtain a pyridyl chlorinated polyethylene film; (2) Mix resorcinol, pyridyl chlorinated polyethylene film, anhydrous aluminum chloride and acetone in a mass ratio of 1:(10-12):(1.2-1.3):(12-15), react at 70-80°C for 5-6h, filter and wash with pure water for 3-4 times, and dry at room temperature for 24h to obtain a pre-modified chlorinated polyethylene film; mix polyformaldehyde and chloroform evenly and heat to 40°C, add calcium hydride, heat to 70°C, add aminomethyltrimethylsilane under nitrogen protection, heat to 80°C, add the pre-modified chlorinated polyethylene film, react for 20h, take out, wash with pure water 3 times and dry at room temperature for 24h to obtain a modified chlorinated polyethylene film; (3) Vinyl acetate, vinyl quaternary ammonium salt, methanol, and azobisisobutyronitrile are mixed in a mass ratio of 1: (0.2-0.3): (0.7-0.8): (0.01-0.02), and put into a high-pressure reactor. After ethylene is introduced for 5-10 minutes, the pressure of ethylene in the high-pressure reactor is set to 4.0 MPa, the temperature is raised to 55-60° C., and the reaction is carried out at a speed of 150-200 r / min for 4-5 hours. After the reaction is completed, the temperature is lowered to room temperature and the material is discharged. A methanol aqueous solution is used for precipitation, and the mixture is filtered and washed with pure water for 3-4 times. The mixture is dried at 70° C. for 24 hours to obtain a quaternary ammonium salt-ethylene-vinyl acetate copolymer; (4) Paraformaldehyde and N,N-dimethylformamide are mixed uniformly and heated to 40°C, calcium hydride is added, the temperature is raised to 70°C, nitrogen is introduced, 2-tert-butylphenol is added, the temperature is raised to 80°C, quaternary ammonium salt-ethylene-vinyl acetate copolymer is added, the reaction is continued for 20 hours, the filtrate is filtered and retained, N,N-dimethylformamide is removed by vacuum rotary evaporation to obtain a modified ethylene-vinyl acetate copolymer, the modified ethylene-vinyl acetate copolymer is granulated by a granulator, and the granules are compression molded by a flat vulcanizer at 90°C to obtain a modified film; (5) Grinding one side of the non-woven fabric with sandpaper, covering it with a modified adhesive film, then covering it with a polyvinylidene chloride film, then covering it with a modified adhesive film, and then covering it with a modified chlorinated polyethylene film. Repeat the above grinding-covering operation on the other side of the non-woven fabric, and hot rolling it twice on a hot rolling mill. The hot rolling mill pressure is 0.3 MPa, the temperature is 140-150°C, and the time is 3 minutes. After the hot rolling is completed, an anti-tritium composite fabric is obtained.

2. The preparation process of the tritium-proof composite fabric according to claim 1, characterized in that: The 2-chloro-6-vinylpyridine-acetone solution in step (1) is prepared by mixing 2-chloro-6-vinylpyridine and acetone in a mass ratio of 1:(5-6); the model of the polyethylene film is 6098.

3. The preparation process of the tritium-proof composite fabric according to claim 1, characterized in that: The mass ratio of the polyformaldehyde, aminomethyltrimethylsilane, pre-modified chlorinated polyethylene film, calcium hydride and chloroform in step (2) is 1:(1.6-1.8):(10-12):(0.7-0.8):(20-30).

4. The preparation process of the tritium-proof composite fabric according to claim 1, characterized in that: The preparation process of the vinyl quaternary ammonium salt in step (3) is as follows: at 0°C, N,N-dimethylethylenediamine, di-tert-butyl dicarbonate, and dichloromethane are mixed in a mass ratio of 1:(0.6-0.7):(20-30) for 10-15 minutes, stirred at 20°C for 24 hours, and pure water of an equal volume to dichloromethane is added, and the liquids are separated and the organic phase is retained; vinyl chloride of 0.9-1.0 times the mass of N,N-dimethylethylenediamine and potassium carbonate of 0.2-0.3 times the mass of N,N-dimethylethylenediamine are added to the organic phase, and the temperature is raised to 7 Reflux at 0-80°C for 10-12h, after the reaction is completed, remove dichloromethane by vacuum rotary evaporation to obtain a vinyl quaternary ammonium salt precursor; at 0-4°C, mix the vinyl quaternary ammonium salt precursor and dichloromethane in a mass ratio of 1:(10-12), add trifluoroacetic acid 5-7 times the mass of the vinyl quaternary ammonium salt precursor dropwise at a dropping speed of 1mL / min, after the addition is completed, heat to room temperature and continue to react for 3-4h, after the reaction is completed, add saturated sodium carbonate solution to adjust the pH to 9-10, and remove dichloromethane by vacuum rotary evaporation to obtain a vinyl quaternary ammonium salt.

5. The preparation process of the tritium-proof composite fabric according to claim 1, characterized in that: The methanol-water solution in step (3) is prepared by mixing methanol and water in a mass ratio of 3:

1.

6. The process for preparing a tritium-proof composite fabric according to claim 1, characterized in that: The mass ratio of the paraformaldehyde, 2-tert-butylphenol, quaternary ammonium salt-ethylene-vinyl acetate copolymer, calcium hydride and N,N-dimethylformamide in step (4) is 1:(3.4-3.5):(0.2-0.3):(0.7-0.8):(20-30).

7. The preparation process of the tritium-proof composite fabric according to claim 1, characterized in that: The thickness of the modified film in step (4) is 0.5 mm.

8. The process for preparing a tritium-proof composite fabric according to claim 1, characterized in that: The model of the non-woven fabric in step (5) is 1473R; the model of the polyvinylidene chloride film is VSL-4603.

Citation Information

Patent Citations

  • Coating composition containing benzoxazine functionalized micro / nano-spheres, and use thereof

    CN107513347A

  • Linear low-density stretch-proof wrapping film and preparation method thereof

    CN114736449A

  • Multilayer articles comprising resorcinol arylatepolyester and method for making thereof

    KR1020050023226A